2021
DOI: 10.1186/s13008-021-00076-7
|View full text |Cite
|
Sign up to set email alerts
|

ROMO1 is required for mitochondrial metabolism during preimplantation embryo development in pigs

Abstract: Background Reactive oxygen species (ROS) modulator 1 (ROMO1) is a mitochondrial membrane protein that is essential for the regulation of mitochondrial ROS production and redox sensing. ROMO1 regulates ROS generation within cells and is involved in cellular processes, such as cell proliferation, senescence, and death. Our purpose is to investigates the impact of ROMO1 on the mitochondria during porcine embryogenesis. Results We found that high expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
(58 reference statements)
2
9
0
Order By: Relevance
“…In this study, OA supplementation effectively improved the MMP of porcine early embryos, suggesting that OA can strengthen mitochondrial function. These findings are consistent with those of previous research, in which embryos with better mitochondrial function showed better proliferation and development(Niu et al, 2020; Zhou et al, 2021). .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, OA supplementation effectively improved the MMP of porcine early embryos, suggesting that OA can strengthen mitochondrial function. These findings are consistent with those of previous research, in which embryos with better mitochondrial function showed better proliferation and development(Niu et al, 2020; Zhou et al, 2021). .…”
Section: Discussionsupporting
confidence: 93%
“…In this study, OA supplementation effectively improved the MMP of porcine early embryos, suggesting that OA can strengthen mitochondrial function. These findings are consistent with those of previous research, in which embryos with better mitochondrial function showed better proliferation and development (Niu et al, 2020;Zhou et al, 2021).. In summary, this study suggested that supplementation of the IVC medium with 2.5 μM of OA could augment the quality of early embryos and enhance blastocyst rates and total cell numbers.…”
Section: Oa Ameliorates Mitochondrial Function During Early-stage Por...supporting
confidence: 92%
“…As previously report [ 23 ], a total of approximately 100 porcine oocytes per group were lysis with 10 μl RIPA buffer and 10 μl loading buffer, and then heated at 98 C for 10 min. Lysates were separated by 6–12% SDS-PAGE gel and transferred onto polyvinylidene fluoride membranes.…”
Section: Methodsmentioning
confidence: 99%
“…To prepare ATF7 dsRNA, ATF7 was amplified using a pair of primers containing the T7 promoter sequence ( ATF7 dsRNA: forward, TAA TAC GAC TCA CTA TAG GGG GGC TAT GAT CCA CTT CAC CC; reverse, TAA TAC GAC TCA CTA TAG GGG CTC ATC CGG ATC TTC ATC CA). The purified PCR products were used to synthesize dsRNA using the MEGAscript T7 Kit (AM1333; Thermo Fisher Scientific, Waltham, MA, USA) according to the manufacturer's instructions 32,33 . After in vitro transcription, dsRNA was treated with DNase I and RNase A to remove the DNA template and any single‐stranded RNA, followed by purification by phenol–chloroform extraction and isopropyl alcohol precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…The purified PCR products were used to synthesize dsRNA using the MEGAscript T7 Kit (AM1333; Thermo Fisher Scientific, Waltham, MA, USA) according to the manufacturer's instructions. 32 , 33 After in vitro transcription, dsRNA was treated with DNase I and RNase A to remove the DNA template and any single‐stranded RNA, followed by purification by phenol–chloroform extraction and isopropyl alcohol precipitation. The purified dsRNA was dissolved in RNase‐free water.…”
Section: Methodsmentioning
confidence: 99%